5x + 6y = 50
-x + 6y = 26

Elimination

5x+6y=50
-x+6y=26

Make the second problem and multiply everything by -1

5x+6y=50
-1(-x+6y=26)
X-6y=-26
Eliminate the y and combine evrything
6x=24
Divide 6 both sides
X=4
Then substitute the x
-(4)+6y=50
-4+6y=50
Add 4 both sides
6y=54
Divide 6 and y=9 x=4

Multiply one of the equations by -1
5x+6y=50
-1(-x+6y=26) =x-6y=-26
Cancel out the 6y’s add the rest
6x=24
X=4
Substitute x back into the original
-(4)+6y=26
-4+6y=26
6y=30
Y=5
Get the point (4,5)


RELATED: